PERAN PSIKOLOGI POSITIF TERHADAP PENDIDIKAN DI INDONESIA: POSITIVE EDUCATION IN FISIKA - Ramadhanti, Auliya; Nurhayati, Siti Rohmah; Putra, Rahman Pranovri; Ali, Sara Mustafa Sayed (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
Positive education is an implementation of positive psychology which is a study related to happiness and well-being, namely using the PERMA model developed by Seligman in 2011. In the context of education, positive psychology has had a positive impact with the emergence of positive education which has even been adapted by Indonesia's new curriculum, namely Merdeka Belajar. In positive education, our goal is not only to improve student achievement in terms of cognitive and student skills, but how well-being and positive character of students are also a big consideration in order to increase Indonesian students' interest in learning. Not only the teacher's efforts but students have also been introduced to Positive Psychology in order to explore the positive character strengths of students. Future researchers can certainly examine more deeply the use of independent learning in the long term and how it affects learning in schools, especially learning physics.